2009
DOI: 10.1021/je8005503
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of HFC32, HFC125, HFC152a, and HFC143a in Three Polyols

Abstract: The solubility of a blowing agent in a polyol plays an important role in determining the overall quality of the polyurethane foam. For many years, concerns have been raised about the high ozone depleting potential (ODP) of traditionally used blowing agents such as chlorofluorocarbons and hydrochlorofluorocarbons. To this end, hydrofluorocarbons (HFCs) have been identified to be long-term replacements as the future blowing agents. In this study, we chose four HFCs, namely, HFC-125 (1,1,1,2,2-pentafluoroethane),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Deng et al reported the VLE data of the HFC161 + DMF and HFC161 + DMEDEG systems from 293.15 to 353.15 K and then analyzed the performance of the two systems in a composite refrigeration cycle; their results showed that the HFC161 + DMEDEG system exhibits a better cycle performance. Wahlstrom et al measured the solubility of HFC152a in n -eicosane, n -hexadecane, n -tridecane, and 2,6,10,14-tetramethylpentadecane from 293.15 to 363.15 K and HFC152a in n -hexadecane at 303.15–343.15 K. Yelisetty et al studied the solubility of HFC152a in pluracol 975, pluracol 355, and terol 352. Li et al reported the VLE data for HFC152a + dimethyl ether diethylene glycol (DMEDEG), HFC32 + DMAC, and HFC32 + DMEDEG systems from 293.15 to 353.15 K and used the NRTL model to correlate the experimental data, obtaining fairly good agreement between the calculated and experimental thermodynamic data.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al reported the VLE data of the HFC161 + DMF and HFC161 + DMEDEG systems from 293.15 to 353.15 K and then analyzed the performance of the two systems in a composite refrigeration cycle; their results showed that the HFC161 + DMEDEG system exhibits a better cycle performance. Wahlstrom et al measured the solubility of HFC152a in n -eicosane, n -hexadecane, n -tridecane, and 2,6,10,14-tetramethylpentadecane from 293.15 to 363.15 K and HFC152a in n -hexadecane at 303.15–343.15 K. Yelisetty et al studied the solubility of HFC152a in pluracol 975, pluracol 355, and terol 352. Li et al reported the VLE data for HFC152a + dimethyl ether diethylene glycol (DMEDEG), HFC32 + DMAC, and HFC32 + DMEDEG systems from 293.15 to 353.15 K and used the NRTL model to correlate the experimental data, obtaining fairly good agreement between the calculated and experimental thermodynamic data.…”
Section: Introductionmentioning
confidence: 99%
“…For the refrigerant R152a, Wahlstrom and Vamling , have measured the solubility of R152a in n -eicosane, n -hexadecane, n -tridecane, and 2,6,10,14-tetramethylpentadecane at different temperatures. Yelisetty and Visco have reported the solubility of R152a in Pluracol 975, Pluracol 355, and Terol 352. However, the VLE data of R152a + DMF and R152a + DMAC are not available, limiting the author’s literature works.…”
Section: Introductionmentioning
confidence: 99%